Wind induced dynamic responses on hyperbolic cooling tower shells and the equivalent static wind load. Issue 169 (October 2017) - Zhang, Jun-Feng; Ge, Yao-Jun; Zhao, Lin; Zhu, Bing
Abstract: Wind induced dynamic responses on hyperbolic cooling tower (HCT) shells and the equivalent static wind load (ESWL) are prime concerns for structural designers and researchers. Followed the dynamic calculation in time domain, using the wind pressure got from wind tunnel tests, the dynamic effects of internal forces and displacement of HCT shell were illustrated through the peak factor g and gust response factor G . The original 2-D distribution of G along latitude and meridian directions was degenerated reasonably to 1-D distribution just along meridian direction and the 2-D distribution of g to a single value, according to the structure behaviors, characteristics of dynamic responses and structural design principles of HCT shell. Based on these features of HCT shell and degenerations of g and G, a new approach pursuing ESWL was proposed whose objective is the reinforcement amount but not the internal forces. The ESWL is got by simple amplification of the mean wind load with a single parameter γ, but the γ used for the latitude and meridian directions are independent and the former is much larger. This is the actual reflection of the independent structural design and different dynamic effects of internal forces in latitude and meridian directions. Highlights: Characteristics of Wind induced dynamic responses of HCT are illustrated. Structure behaviors and structural design principles of HCT shells are illustrated. Only the maximum peak response along latitude should be focused on. The tower shell is degenerated from 2-D structure to 1-D structures along meridian. A new approach for ESWL is proposed targeting at the reinforcement amount.